الاستفهام في سورة الأنبياء - Nanang Irfan Nawawi; Aceng Milkillah; Syamsul Ma'arif (Center for Research and Community Service (P3M) STAI DR. KH. EZ. Muttaqien Purwakarta, 2021)
Al-Qur'an is the revelation of Allah SWT which was revealed to the Prophet Muhammad as the greatest miracle. One of the virtues of the Qur'an in terms of language can be seen from the question sentences in the Qur'an. In ma'ani science it is called istifham. This research was conducted with the aim of knowing the verses containing istifham in Surah Al-Anbiya, the adawat al-istifham used, and the meaning of istifham contained in it. The texts of the verses of the Qur'an in the letter al-Anbiya which contain istifham are the data sources for this research. Meanwhile, the method used to analyze the data in this study is content analysis, namely by describing facts in the form of verses containing istifham in Surah al-Ancost, then analyzing its intended meaning using the balaghah approach. After analyzing the data, in Surah Al-Anbiya there are 23 verses that contain istifham. Istifham with Hamjah 15 words with different meanings and Istifham with Hal there are 3 words.